The Implementation of an Accounting System: Tunisian Specificity - Baazaoui, Hedi (Copernican Journal of Finance & Accounting, 2026)
This research aims to study the possibility of applying IAS/IFRS in an emerging economy like Tunisia in the presence of two local repositories the TAS 1997 and the simplified accounting system. The research methodology consists of studying the measurement and disclosure accounting practices adopted by Tunisian companies over four distinct periods (2001, 2007, 2021, and 2024) with the aim of identifying the evolution of these practices and the ability of these companies to implement an innovative repository such as IAS/IFRS. The results obtained show that Tunisian companies are too conservative in their choice of valuation methods and are content to disclose only the minimum amount of information. They apply in their majority the Weighted Average Unit Cost method (WAUC) for the valuation of stocks and the linear method for amortization. They record the borrowing costs and exchange differences into expenses and they record the charges according to their nature. They present the income statement and cash flow statement according to the authorized model and do not publish the note on earnings per share. Our contribution to the literature is to assess the degree of success of Tunisian companies in implementing a sophisticated accounting system such as the IAS/IFRS repository. To my knowledge, no study has examined the success rate of IAS/IFRS implementation in an emerging country like Tunisia. Furthermore, previous studies have focused on the adoption of IAS/IFRS, not on their implementation.